Emerging insights into the roles of ANGPTL8 beyond glucose and lipid metabolism - Ye, Huimin; Zong, Qunchuan; Zou, Huajie; Zhang, Ruixia (Frontiers in Physiology, 2023)
Angiopoietin-like protein 8 (ANGPTL8) is a secreted protein predominantly expressed in liver and adipose tissue. ANGPTL8 modulates the clearance of triglycerides (TGs) by suppressing the activity of lipoprotein lipase (LPL) within the plasma. Previous studies found that circulating ANGPTL8 levels were significantly increased in metabolic disorder-related diseases, such as type 2 diabetes mellitus (T2DM), obesity, metabolic syndrome and nonalcoholic fatty liver disease (NAFLD). Whether ANGPTL8 has a direct pathogenic role in these diseases remains to be determined. In this review, we summarize the emerging roles of ANGPTL8 in the regulation of inflammation, tumours, circulatory system-related diseases, and ectopic lipid deposition, which may provide new insights into the diverse functions of ANGPTL8 in various diseases beyond its well-established functions in glucose and lipid metabolism.